Prospective changes in anemia are associated with the incidence and persistence of sarcopenia among older Mexican adults - De La Cruz-Góngora, Vanessa; Salinas-Rodriguez, Aaron; Manrique-Espinoza, Betty (Frontiers in Nutrition, 2024)
Sarcopenia, characterized by loss of muscle mass and strength, is common in old age but can be accelerated by chronic disease, malnutrition, and physical inactivity. Also, the biological changes during aging increase the risk of malnutrition that older adults face. Although the importance of adequate nutrition has been recognized for a long time, its contribution to muscle mass and strength has yet to be studied extensively, and much research in this area is needed. Moreover, whether anemia has a role in the onset or persistence of sarcopenia has yet to be sufficiently explored, and the evidence from the Latin American population is null, even though structural risk factors might be higher than those in high-income countries. All in all, it remains uncertain whether the accumulated risk of persistent anemia affects sarcopenia over time.